A catarse teatral na formação humana - Cunha, Fabricio Moraes (2013)
Based on a theoretical-bibliographical research, this dissertation aims to investigate the relationship between theater and human formation, in a perspective of Critical Theory of Society. The main goal is to understand how the experience with the theater, capable to rouse the cathartic dimension, can contribute with the growth of human formation. The issue that needs answer is related with the possibility of the cathartic process, motivated by the theater, to inspire a formation opposed to the educational commands linked to the logic of the market. The concept of human development adopted is linked to the concept of Bildung in the philosophical tradition of Theodor W. Adorno. The methodological course starts with a brief conceptual detour in reference works (general and specialized dictionaries) in the areas of philosophy, arts and theater, and then focuses on a literature review, with emphasis on academic papers published by researchers in the educational area and the dialogue with the area of theater studies. The specific goal in this first stage of the work was to understand how the concept of catharsis has been reference in these studies and how, in the academic environment, this has been dialogue between theater and education, knowing that the cathartic experience is the mediation. However, besides knowing the different meanings of catharsis , is important to identify the characteristics of education types that we support in our hypothesis. Therefore, the second specific objective of the work is to understand the educational proposal towards emancipation based on the conceptual framework of Theodor Adorno. As a way to establish a counterpoint between Adorno s assumptions and the current socio-historical context, we also assume the specific purpose of analyzing aspects of the kind of catharsis stimulated by current society and its consequences for the processes of human development. Finally, we investigated how other kind of catharsis, specifically aesthetic and promoted by theatrical art, can serve to Emancipatory Education based on Adorno's Aesthetic Theory